Shift work is associated with extensively disordered sleep, especially when working nights - Boersma, G. J.; Mijnster, T.; Vantyghem, P.; Kerkhof, G. A.; Lancel, Marike (Frontiers in Psychiatry, 2023)
Background: Shift work is generally associated with working and sleeping out of phase with the endogenous, circadian sleep-wake cycle. This exerts detrimental effects on sleep health. The present study aimed at evaluating the presence of short and long sleep as well as sleep disorders within a broad range of shift work schedules and elucidating the role of sociodemographic factors therein.A large dataset containing information on sleep was collected through advertisement in a Belgium newspaper (De Standaard). Adult, working individuals were selected (n=37662) and categorized based on their work schedule (regular day, early morning, evening, night, and rotating shift). In this cross-sectional study, Pprevalence rates of short sleep (≤6 hours), long sleep (≥9 hours) and sleep disorders (screened with Holland Sleep Disorders Questionnaire), and associations between these sleep variables and sociodemographics (age, sex, education, living companion(s)) were analyzed using binominal logistic regression analyses.In the total sample all sociodemographic factors affected prevalences of short, long and disordered sleep, consistent with previous studies. Compared to day workers (26%), shift workers more frequently reported short sleep, most prominently night workers (26 vs 50%) (p<0.001). Furthermore, all sleep disorders as well as sleep disorder comorbidity were more common in shift workers, again most pronounced in night workers (all p<0.05). In night shift workers the level of education had the strongest associations with disturbed sleep with a two-fold higher prevalence of disturbed short and disordered sleep in low relative to academic educated groups (all p<0.02).Conclusions: Shift work is related not only to curtailed sleep and shift work disorder, but also to a plethora of sleep disorders, including insomnia, sleep-related breathing disorders and sleep-related movement disorders. Our findings imply that education on coping strategies may be especially important for young and/or lower educated shift workers.